Self-Awareness, Ethics and Political Society in the Cultural Tradition of the Early Modern Age (Memorandum: Memória e História em Psicologia, 2009)
Exploring the value of images as documents that reveal the culture of the world that produces them, this paper reflects on the relations that were established between the Christian tradition and the development of modernity in Western Europe, particularly in the Catholic area. With reference to the themes of selfawareness, ethics and political society, it criticizes the idea that there was an early divorce and a purely conflictual relationship between religion and the modern world, showing how the construction of the early modern age  accommodated a dialogue that long remained fertile between the two parts. What the modern world was, at least in its beginnings, including its affirmation of the value of the human person, of material and cultural progress, is inseparable from the way it embraced and developed the content of the Christian vision of man and reality.